The Implementation Of Facilities Management In University Science Malaysia - Mohd, Noor Hafiza (Universiti Sains Malaysia, 2005)
The purpose of this research is to examine the implementation of Facilities Management in University Science Malaysia. This study concentrates on University Science Malaysia as a unit of analysis and is focused on findings the level of implementation of Facilities Management in a university.